ANALISIS KINERJA ORGANISASI DALAM MEWUJUDKAN PELAYANAN BERKUALITAS KEPADA PENGURUS UNIT KEGIATAN MAHASISWA (UKM) UNIVERSITAS NEGERI MALANG (UM) - Nida Anisatus Sholihah (Universitas Negeri Malang, 2021)
Abstract: Administrative service is described as one, staff or employee’s effort to process and implement everything by determining the method of organizing, building up the organization that suitable with the implementation of policies to accomplish predetermined goals. The objectives of this Study are: (i) to analyze the organizational performance in manifesting the quality of the services toward the Student Activity Unit administrators and; (ii) to analyze what factors support and hinder the performance of UM Student Affairs administrative staff. This study is considered descriptive qualitative research. It is conducted at the Student Affairs Division. The main data source is the Head of Sub Division and administrative staff as and the secondary data source is Student Activity Unit administrators at Universitas Negeri Malang (UM). The data is acquired using interviews, field notes, questionnaires, question lists, and documentation. Meanwhile, the data is analyzed using reduction, presentation of data, and verification or concluding. The result of this study shows that: (i) the quality of the administrative staff or employee at the Student Affairs Division is categorized as good. It matched with the regulation of the Rector of Universitas Negeri Malang. The service toward Student Activity Unit administrators suits to the predetermined SOP, friendly, and corresponds with the predetermined goal; (ii) the factors that support the performance of the Student Affairs Division are the implementation of the Secretarial Workshop for Student organization administrators, the effectiveness of time service, and the speed and accuracy of the Student Activity Unit administrators in making proposals and submitting the accountability of reports funds. While the factors that hinder the performance are the slow pace of Student Activity Unit administrators in making proposals and submitting the accountability of reports funds, lack of understanding of the Student Activity Unit administrators in submitting the project activity proposals, and making the accountability of reports funds. Keywords: performance; administrative services; student activity unit. Abstrak: Layanan administrasi merupakan usaha seseorang, staf atau pegawai dalam rangka memproses dan melaksanakan segala sesuatu dengan penetapan cara-cara penyelenggaraan pembinaan organisasi sesuai dengan penyelenggaraan kebijakan untuk mencapai tujuan yang telah ditentukan. Tujuan penelitian ini adalah untuk: (i) menganalisis kinerja organisasi dalam mewujudkan pelayanan yang berkualitas kepada pengurus Ormawa Unit Kegiatan Mahasiswa (UKM) dan; (ii) menganalisis faktor-faktor apa saja yang menjadi pendukung dan penghambat kinerja staf administrasi bagian Kemahasiswaan UM. Penelitian ini merupakan jenis penelitian deskriptif kualitatif yang dilaksanakan di Bagian Kemahasiswaan Universitas Negeri Malang (UM) dengan sumber data primer Kasubag dan Staf administrasi Subbag MPIKA UM dan sumber data sekunder yaitu pengurus UKM di UM. Data diperoleh dengan cara wawancara, catatan lapangan, penyebaran kuesioner dan daftar pertanyaan, dan dokumentasi. Sedangkan analisis data dilakukan dengan cara reduksi, penyajian data, dan verifikasi atau penarikan kesimpulan. Hasil penelitian menunjukkan bahwa: (i) kinerja staf administrasi atau pegawai di bagian Kemahasiswaan UM termasuk kategori baik dan berkualitas karena sesuai dengan peraturan Rektor UM. Pelayanan kepada pengurus UKM telah sesuai dengan SOP yang telah ditetapkan, ramah, dan sesuai dengan target yang telah ditetapkan; (ii) faktor-faktor yang menjadi pendukung kinerja Kemahasiswaan adalah penyelenggaraan kegiatan Workshop Kesekretariatan bagi pengurus Ormawa, waktu pelayanan yang efektif, serta kecepatan dan ketepatan pengurus UKM dalam membuat proposal kegaitan dan penyerahan laporan pertanggungjawaban dana. Sedangkan faktor penghambatnya adalah lambatnya pengurus UKM dalam pembuatan proposal kegaitan dan penyerahan laporan pertanggungjawaban dana, tidak pahamnya pengurus UKM dalam pengajuan proposal kegiatan dan pembuatan laporan pertanggungjawaban dana. Kata kunci: kinerja; layanan administrasi; unit kegiatan mahasiswa.